MEMS Dynamic Characteristics Analysis of Electrostatic Microbeams for Building Structure Monitoring. (19th January 2022) - Gong, Youping; Bo, Hong; Zhou, Chuanping; Wang, Maofa; Zhou, Rougang
Abstract : Building structure health monitoring is essential for modern buildings, sensors related to building structure health monitoring are often made with microelectrostatic cantilever beam (MECB), and the performance of this kind of devices is often affected by instability, which affects the measurement results and accuracy. Therefore, it is necessary to study the nonlinear dynamic characteristics of the MECB in the process of bending and pull-in. In this paper, based on the energy principle and fluid pressure film damping effect, the dynamic equation mathematical model of MECB is established and then the dynamic characteristics of the pull-in and lift-off voltage of the MECB and the harmonic motion characteristics under the bias voltage are obtained, which provides guidance for the design of the electrostatic driving sensor.